Lactobacillus rhamnosus accelerates zebrafish backbone calcification and gonadal differentiation through effects on the GnRH and IGF systems. - Matteo A Avella; Allen Place; Shao-Jun Du; Ernest Williams; Stefania Silvi; Yonathan Zohar; Oliana Carnevali (PLoS ONE)
Endogenous microbiota play essential roles in the host's immune system, physiology, reproduction and nutrient metabolism. We hypothesized that a continuous administration of an exogenous probiotic might also influence the host's development. Thus, we treated zebrafish from birth to sexual maturation (2-months treatment) with Lactobacillus rhamnosus, a probiotic species intended for human use. We monitored for the presence of L. rhamnosus during the entire treatment. Zebrafish at 6 days post fertilization (dpf) exhibited elevated gene expression levels for Insulin-like growth factors -I and -II, Peroxisome proliferator activated receptors -α and -β, VDR-α and RAR-γ when compared to untreated-10 days old zebrafish. Using a gonadotropin-releasing hormone 3 GFP transgenic zebrafish (GnRH3-GFP), higher GnRH3 expression was found at 6, 8 and 10 dpf upon L. rhamnosus treatment. The same larvae exhibited earlier backbone calcification and gonad maturation. Noteworthy in the gonad development was the presence of first testes differentiation at 3 weeks post fertilization in the treated zebrafish population -which normally occurs at 8 weeks- and a dramatic sex ratio modulation (93% females, 7% males in control vs. 55% females, 45% males in the treated group). We infer that administration of L. rhamnosus stimulated the IGF system, leading to a faster backbone calcification. Moreover we hypothesize a role for administration of L. rhamnosus on GnRH3 modulation during early larval development, which in turn affects gonadal development and sex differentiation. These findings suggest a significant role of the microbiota composition on the host organism development profile and open new perspectives in the study of probiotics usage and application.